DESIGNING A PRE-LAUNCH DIGITAL MARKETING STRATEGY BASED ON CONSUMER INSIGHT, CUSTOMER JOURNEY, AND VALUE PROPOSITION TO ENHANCE BRAND AWARENESS OF A DIGITAL JOURNALING PLATFORM - Iqbal Zainul Muttaqin (PT. Jurnal Center Indonesia Publisher, 2026)
The development of digital platforms in the mental health sector has shown significant growth, along with increasing awareness among younger generations regarding the importance of self-reflection and psychological well-being. One type of service with the potential to address these needs is digital journaling platforms. However, at the pre-launch stage, the main challenge faced by digital platforms lies not only in feature design, but also in building brand awareness from the outset through digital marketing strategies that are relevant to the needs of potential users.This study aims to design a digital marketing strategy based on consumer insight, customer journey, and value proposition at the pre-launch stage of the PelanPelan digital journaling platform. The study adopts a descriptive qualitative approach involving potential users from Generation Z aged 20–28 years. Data were collected through semi-structured interviews and open-ended surveys. The data were analyzed using thematic analysis to identify consumer insights, construct a conceptual customer journey, and formulate a value proposition as the foundation of the digital marketing strategy.The findings indicate that potential users perceive journaling as a tool for emotional regulation and self-reflection, yet still experience adoption barriers at the awareness stage. Based on these findings, pre-launch digital marketing strategies should focus on empathetic, simple, and emotionally driven communication to build contextual brand awareness.